Comparative Evaluation of the Effectiveness of Standard and Non-standard Computer Perimetry Methods in the Early Diagnosis of Glaucoma - Simakova, I. L.; Kulikov, A. N.; Serdyukova, S. A.; Tikhonovskay, I. A. (Oftalmologii͡a, 2025)
Purpose: tо compare the effectiveness of standard automated perimetry (SAP) and two non-standard perimetry methods in the diagnosis of the early stage primary open-angle glaucoma (POAG). Patients and methods. The study involved 18 patients (32 eyes) with the early POAG, 10 women, 8 men (average age of 56.2 ± 1.4 years). The control group included 32 healthy people (32 eyes), (average age of 56.4 ± 3.9 years). In addition to the routine ophthalmic examination all subjects underwent SAP (Octopus 900, threshold strategy “G TOP”) and two methods of non-standard perimetry — the author’s own modification of Frequency Doubling Technology (FDT) Perimetry (threshold strategies “FDT-16” and “FDT-64”) and Pulsar perimetry (Octopus 600). Morphometric assessment of the optic nerve head was performed using stereoophthalmoscopy and retinotomography (Heidelberg Retina Tomograph 3 and RTVue FD-OCT). Optical coherence tomography was also used to assess the parameters of the retinal ganglion cell complex in the macular region. Results. Evaluating the sensitivity level of these 4 compared strategies (“FDT-16”, “FDT-64”, “Pulsar” Octopus 600 and “G TOP” Octopus 900) in patients with the early stage of POAG by mean MD index (87.1, 93.55, 54.84 and 80.65 % respectively) and by mean number of 10×10° squares with scotomas in the central visual field (90.32, 98.77, 51.61, and 83.87 % respectively) showed that both threshold FDT perimetry strategies were 7 to 15 % higher than the sensitivity of Octopus 900 (“G TOP”) and almost 2 times higher than the sensitivity of Octopus 600 (“Pulsar”). The specificity level of all three threshold strategies (“FDT-16”, “FDT-64” and “Pulsar”) of both non-standard perimetry methods was 100 %, and specificity level of SAP was 96.77 %. The correlation between the values of the MD index and the number of squares with scotomas in the central visual field according to the SAP data and all three threshold strategies data of the two non-standard perimetry methods was moderate and statistically significant. Conclusion. For diagnosis of early POAG a combination of standard and non-standard computer perimetry methods is advisable. Both FDT perimetry strategies had a significant advantage in the sensitivity level of their results compared to Pulsar perimetry data.